Saving, Investment, Financial Integration, and the Balance of Payments. (IMF Working Papers; Working Paper ;, 1989)
This paper examines the extent of international financial integration, and its consequences for the current account. The evidence indicates that financial liberalization in the 1970s and 1980s has resulted in a substantial movement towards closer integration of world capital markets. By reducing constraints on international capital flows, this movement makes the current account more of a residual factor in agents' decisions.